2008
DOI: 10.3174/ajnr.a1257
|View full text |Cite
|
Sign up to set email alerts
|

Renal Safety of CT Angiography and Perfusion Imaging in the Emergency Evaluation of Acute Stroke

Abstract: BACKGROUND AND PURPOSE:Multimodal CT imaging with contrast-enhanced CT angiography (CTA) and CT perfusion (CTP) is increasingly being used to guide emergency management of acute stroke. However, little has been reported about the safety of intravenous contrast administration associated with these studies in the acute stroke population, including cases in which baseline creatinine values are unknown. We investigated the incidence of contrast-induced nephropathy (CIN), defined as a 25% or more increase in baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 30 publications
3
71
2
3
Order By: Relevance
“…In most centres, computed tomographic angiography (CTA) is the modality of choice owing to widespread availability, speed of image acquisition, and minimal contraindications in patients without renal impairment. 17 It is important to note that neither CT nor CTA is highly sensitive for the diagnosis of acute posterior fossa ischemic stroke; one study found that only 33% of acute MRI-confirmed brainstem infarctions were detected by CT.…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…In most centres, computed tomographic angiography (CTA) is the modality of choice owing to widespread availability, speed of image acquisition, and minimal contraindications in patients without renal impairment. 17 It is important to note that neither CT nor CTA is highly sensitive for the diagnosis of acute posterior fossa ischemic stroke; one study found that only 33% of acute MRI-confirmed brainstem infarctions were detected by CT.…”
Section: Diagnosis and Managementmentioning
confidence: 99%
“…The use of this technique is supported by the current literature 4,[6][7][8][9] . Delgado-Almandoz et al 4,15 defined CTA-SI parameters appropriate for the diagnosis of the spot sign within ICH.…”
Section: Discussionmentioning
confidence: 73%
“…This imaging sign has also been reproduced on MDCT angiography as a robust predictor of expansion and as an indicator of worse prognosis and mortality 3,4 . MDCT angiography has been proven to be a rapid and reproducible alternative to catheter angiography that reduces the risks to the enrolled patients and offers significant benefits to the decision-making process [6][7][8][9] . A higher incidence of hemorrhagic stroke has been repor ted in the Latin American population [10][11][12][13] .…”
mentioning
confidence: 99%
“…CT angiography is a less invasive and valuable tool in the diagnosis of vascular pathologies, and has spread rapidly with the application of new technologies, such as multi-detector CT. 8,14) One of the advantages of this method is that comprehensive vascular anatomic data can be obtained in a single examination. Thus, useful and important information for planning the treatment strategy can be provided by mapping out the arterial anatomy prior to intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies focusing on imaging with contrast medium demonstrated much lower incidence of renal failure due to contrast medium-induced nephropathy. 8,9) However, we should perform CT angiography with a protocol intended to decrease intravenous administration of contrast medium as much as possible.…”
Section: Discussionmentioning
confidence: 99%